Utilizing content analysis in teaching materials for children with autism spectrum disorder - Malay, Tara (2019)
It is important to look at how education materials for students with disability view disability itself. Raising the general public's awareness on autism is crucial because of the rise in the antivaxx and anti-science movements, particularly in the United States. This thesis utilizes Content Analysis to explore how a set of teaching materials for students with Autism Spectrum Disorder (ASD) understands ASD and the agency of the ASD child and creates trust with the readers. I analyze two argumentation styles to understand how those forms of argumentation create trust with the readers. This study is qualitative and relies on philosophical and cultural definitions of agency and personhood. In addition, this thesis also gives a brief background on the history of autism diagnosis and disability terminology. The cultural setting of the thesis is the United States. This research helps shed light on the content of education materials for disabled children and how that content can shape the general public's opinion on Autism Spectrum Disorder.